Penggunan Simulator Virtual Untuk Meningkatkan Pemahaman Dan Keterampilan Peserta Didik Dalam Materi Pengukuran - Hesti Dwi Utari (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
This study aims to improve students' understanding and skills in using measuring instruments, especially screw micrometers and calipers, using a virtual simulator. The research method used is a qualitative method using a Problem Based Learning (PBL) learning model based on Technological Pedagogical Content Knowledge (TPACK). Collecting research data using cognitive assessment instruments in the form of written tests, performance assessments, and learning reflection questionnaires. This article is a best practice carried out in the odd semester of the 2022/2023 academic year for class X science students. The use of this learning strategy gave positive results, including (1) Students' understanding of how to use caliper and screw micrometers was better, (2) Students' skills in measuring practice, especially length measurement, increased, (3) More learning activities effective in terms of time, (4) Being a solution to the limited number of measuring instruments owned by the school, (5) Increasing the enthusiasm of students in learning, (6) Increasing students' critical thinking. The results obtained are in line with the results of several similar studies using virtual learning aids.